The Implementation of the Graphic Organizer Technique in Teaching Storytelling to Improve Students' Speaking Ability - Nuhla Fauziyyatun Nabilah; Erwin Hari Kurniawan; Wildan Isna Ashyar (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2022)
The graphic organizer is a technique that uses by organizing structural knowledge in the form of diagrams, maps, or charts. Some previous studies have proved the effectiveness of using graphic organizers in teaching writing. However, this research used a graphic organizer to improve students' speaking ability through storytelling. Therefore, the goal of this study is: (1) to know the students' speaking ability before participating in learning activities using graphic organizers, (2) to know the students' speaking ability after participating in learning activities using graphic organizers, and (3) knowing the effect of graphic organizers technique in storytelling to improve student's English speaking ability. By using the pre-experimental method one class pre and post-test, the researcher collected the data by conducting tests before and after giving treatment graphic organizer. After collecting the data and computing the number by using SPSS 23 version, the result showed that: (1) The students' speaking score in storytelling from the pre-test is categorized as low and fair. The highest score is 68 with a mean of score 52.64. (2) The students' speaking score in storytelling from the post-test is good. The highest score is 86 with a mean of score 79.80. (3) There is an effect of graphic organizers on students' speaking ability in storytelling. Through the result above, it was suggested that graphic organizers must be applied in Mr. Language Education Center to help improve students' speaking abilities in a basic class. The students were also able to try making graphic organizers before the speaking test to ease them in understanding the content. Moreover, the next researcher able to use this research as a reference to conduct similar research in the future.